The co-development and pilot evaluation of the Siblings Training, Empowerment, and Advocacy Kit (Siblings TEAKit) to support youth and young adult siblings of individuals with a disability: A participatory action research qualitative study protocol - Linda Nguyen; Samantha Bellefeuille; Hanae Davis; Jan Willem Gorter; Marjolijn Ketelaar; Jennifer Zwicker; Keiko Shikako (Research Involvement and Engagement)
Abstract Introduction Siblings can have multiple roles in the lives of each other over time, including the roles of friend, role model, and caregiver at different time points. These roles may be different for siblings of youth with disabilities, and yet, there are limited resources to support siblings in the health, rehabilitation, and education systems. This protocol outlines a study for which the primary aim is to develop and evaluate a toolkit to support youth and young adult siblings to initiate conversations about their roles and responsibilities with their sibling(s) with a disability and family. The secondary aim of the study is to test a framework for and evaluate the process of partnered research with siblings and other family members. Methods This qualitative descriptive study will adopt a participatory approach where a Sibling Youth Advisory Council (SibYAC) of young adult siblings of individuals with a disability and/or chronic health condition will be engaged as research partners. The long standing partnership with the SibYAC and our team has informed the need to conduct this study. This study will be conducted in two stages to address our primary aim. First, a co-design workshop will be held with siblings (ages 14 to 25 years old) to develop the content and format of the toolkit. Second, focus groups will be conducted with siblings, parents, and healthcare professionals to provide feedback on the toolkit prototypes. Data will be analyzed using directed content analysis with implementation science frameworks as a guide. Specifically, the Theoretical Domains Framework and COM-B model will be used to identify toolkit elements focused on supporting siblings, and the Consolidated Framework for Implementation Research (CFIR) will provide considerations about settings for where the toolkit could be implemented in the future. The secondary aim is addressed where our partnership with the SibYAC will be evaluated through formative discussions and the Public and Patient Engagement Evaluation Tool. Discussion This study protocol advances the methods and rigour in participatory research with young people, including siblings. This study is the first step towards the development of a toolkit to support siblings of persons with disabilities to foster dialogue between families, health and education professionals about their roles. Clear expectations about family roles can promote positive health and wellbeing for siblings and the whole family.